Efeito hall de spin inverso em multicamadas de Ta/NiFe/FeMn/Ta - Garcia, Wagner Jesus da Silva (2017)
In the present thesis, the generation of a dc voltage in exchange-biased Ta/NiFe/FeMn/Ta multilayers at ferromagnetic resonance was investigated. This dc signal is related to two distinct phenomena, namely, the spin rectification effect (SRE) and the inverse spin Hall effect (ISHE). The first comes from a non-linear coupling between a dynamic electric current and a dynamic electrical resistance induced by a microwave magnetic field via anisotropic magnetoresistance (AMR) and anomalous Hall effect (AHE). The sencond refers to the transformation of a pure spin current into a charge current caused by spin dependent scattering processes. Two methods were used to discriminate between SRE and ISHE contributions. The universal method explores the dependence of those effects with the spin injection direction. The angular method envolves an angular sweeping, where the in-plane static magnetic field direction is varied, and for each angle H, VDC(H) is measured. Among all produced samples, that with the highest exchange bias field was chosen to conduct the investigation and separate the contribution of the ISHE signal from SRE by both methods. The ISHE contribution was confirmed by equivalence between the universal and angular methods for separation of the ISHE signal.